2011
DOI: 10.1186/1475-2891-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Poor nutritional status of schoolchildren in urban and peri-urban areas of Ouagadougou (Burkina Faso)

Abstract: BackgroundMalnutrition is still highly prevalent in developing countries. Schoolchildren may also be at high nutritional risk, not only under-five children. However, their nutritional status is poorly documented, particularly in urban areas. The paucity of information hinders the development of relevant nutrition programs for schoolchildren. The aim of this study carried out in Ouagadougou was to assess the nutritional status of schoolchildren attending public and private schools.MethodsThe study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
100
9
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 40 publications
22
100
9
2
Order By: Relevance
“…These high rates were similar to the observations from previous studies 5, 6,11 . Assefa et al 16 also reported anaemia prevalence of 30.1% among 12-14 year old school children in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These high rates were similar to the observations from previous studies 5, 6,11 . Assefa et al 16 also reported anaemia prevalence of 30.1% among 12-14 year old school children in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
“…The higher prevalence of stunting (P<0.05) among the 12-14 years was a surprise and contradicts previous studies 11,26 in which stunting affected older school children more than younger ones. The reason for this could not be ascertained but the researchers attributed it to the fact that this age group may have had severe nutritional deprivation when they were younger (in the first few years of life) than the older children.…”
contrasting
confidence: 88%
See 2 more Smart Citations
“…Em conformidade com os dados desta pesquisa, em estudo realizado no Ceará 32 , com indivíduos na faixa etária dos dois aos 97 meses, os níveis séricos de retinol e de zinco não apresentaram diferenças estatísticas considerando a faixa etária das crianças. Na Paraíba, em pesquisas realizadas com pré-escolares, a idade não apresentou Revista 39 , incluindo a coexistência da deficiência de vitamina A e anemia, que foi a de maior proporção no presente trabalho. As proporções das coexistências reportadas nos estudos anteriores diferem de um estudo para outro.…”
Section: I S C U S S ã Ounclassified